2017
DOI: 10.1103/physrevb.95.104412
|View full text |Cite
|
Sign up to set email alerts
|

E -type noncollinear magnetic ordering in multiferroic oLuMnO3

Abstract: Multiferroic orthorhombic o-LuMnO 3 exhibits large ferroelectric polarization induced by an E-type magnetic order. Recently, the E-type magnetic phase in LuMnO 3 was proposed to feature magnetic moments tilted away from the collinear ordering. We employed neutron diffraction to determine the symmetry of the magnetic order in o-LuMnO 3. We observed that below T N = 39 K, the Mn 3+ spins order into an incommensurate amplitudemodulated phase that obeys the Pbnm crystal symmetry and is paraelectric. The incommensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…We want to point out that the large P values ∼1 μC/cm 2 at T = 37.5 K) observed in thin strained TbMnO 3 films originate from a combined effect of symmetric (S • S)-type exchange striction for E-type CM order and an antisymmetric (S × S)-type Dzyaloshinskii-Moriya interaction of the abspiral ICM order. Similar contributions to the FE polarization are observed in bulk Eu 1−x Y x MnO 3 and Y 1−y Lu y MnO 3 [11].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We want to point out that the large P values ∼1 μC/cm 2 at T = 37.5 K) observed in thin strained TbMnO 3 films originate from a combined effect of symmetric (S • S)-type exchange striction for E-type CM order and an antisymmetric (S × S)-type Dzyaloshinskii-Moriya interaction of the abspiral ICM order. Similar contributions to the FE polarization are observed in bulk Eu 1−x Y x MnO 3 and Y 1−y Lu y MnO 3 [11].…”
Section: Discussionsupporting
confidence: 76%
“…Since the (0 1 0) reflection is forbidden for an orthorhombic symmetry, the existence of the (0 1 0) reflection in orthorhombic YMnO 3 was taken as evidence for the magnetic E-type order. A symmetry analysis for o − RMnO 3 confirmed that the existence of a forbidden nonmagnetic structural reflection implies purely a breaking of the rotational symmetry element along the b axis (2 b ) [11]. This symmetry argument is supported by the simultaneous appearance of ferroelectric ordering and the (0 1 0) reflection.…”
Section: Introductionmentioning
confidence: 76%
“…Neutron diffraction gives access to a large Ewald sphere and enables us to measure the intensity of Q = (0 q 1) reflection for the family of strained o-RMnO 3 (R = Gd-Lu) thin films. Magnetic structure factor calculations indicate that the (0 q 1) reflection is one of the strongest magnetic reflections of the observed ground state in o-RMnO 3 , such as a spiral or an E-type phase [4,27]. The measured intensity of the magnetic reflections is sensitive to the projection of the magnetization components normal to Q.…”
Section: Neutron Diffraction Studiesmentioning
confidence: 99%
“…[25], all films show a compressive strain along the a axis while the strain along the c axis varies with the radius of the R ions. The films are compressively strained along c for R = Gd-Dy, and have a tensile strain for [34,56,57], TbMnO 3 [4,34], DyMnO 3 [34,58], HoMnO 3 [26,34], ErMnO 3 [29], TmMno 3 [39], YbMnO 3 [28,38], LuMnO 3 [27], and T FE of RMnO 3 films [24,25], and T N of TbMnO 3 film [24].…”
Section: A Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation